(untitled) (Sains Humanika, 2009)
This paper compares the classification and management of non-performing loans between Islamic banks in Malaysia and conventional banks in the UK and Japan. The objective of this paper is to investigate if there are differences in the classification and management of non–performing loans in Islamic banks as a result of the existence of the Investment Account Depositors (IADs). The nature of profit and sharing loss agreement has made the position of IADs in an Islamic bank unique. This uniqueness, however, has posed some degree of risk where in case the bank incurs a loss, the IADs are liable to share this loss. This has made the investment of IADs very risky and is subject to the potential problem of asymmetric information. This paper finds that the Islamic banks define and manage their non–performing loans differently from the conventional banks in the UK and Japan. The analysis shows that even though Islamic banks have special characteristics, the classification and management of its non–performing loans are quite lenient. This is evidenced in the way non–performing loans are defined, the way loss provision is made and the level of disclosure made by an Islamic bank.